IRS-2 Partially Compensates for the Insulin Signal Defects in IRS-1(−/−) Mice Mediated by miR-33 - Tang, Chen-Yi (Mol Cells, 2017)
Insulin signaling is coordinated by insulin receptor substrates (IRSs). Many insulin responses, especially for blood glucose metabolism, are mediated primarily through Irs-1 and Irs-2. Irs-1 knockout mice show growth retardation and insulin signaling defects, which can be compensated by other IRSs in vivo; however, the underlying mechanism is not clear. Here, we presented an Irs-1 truncated mutated mouse (Irs-1(−/−)) with growth retardation and subcutaneous adipocyte atrophy. Irs-1(−/−) mice exhibited mild insulin resistance, as demonstrated by the insulin tolerance test. Phosphatidylinositol 3-kinase (PI3K) activity and phosphorylated Protein Kinase B (PKB/AKT) expression were elevated in liver, skeletal muscle, and subcutaneous adipocytes in Irs-1 deficiency. In addition, the expression of IRS-2 and its phosphorylated version were clearly elevated in liver and skeletal muscle. With miRNA microarray analysis, we found miR-33 was down-regulated in bone marrow stromal cells (BMSCs) of Irs-1(−/−) mice, while its target gene Irs-2 was up-regulated in vitro studies. In addition, miR-33 was down-regulated in the presence of Irs-1 and which was up-regulated in fasting status. What’s more, miR-33 restored its expression in re-feeding status. Meanwhile, miR-33 levels decreased and Irs-2 levels increased in liver, skeletal muscle, and subcutaneous adipocytes of Irs-1(−/−) mice. In primary cultured liver cells transfected with an miR-33 inhibitor, the expression of IRS-2, PI3K, and phosphorylated-AKT (p-AKT) increased while the opposite results were observed in the presence of an miR-33 mimic. Therefore, decreased miR-33 levels can up-regulate IRS-2 expression, which appears to compensate for the defects of the insulin signaling pathway in Irs-1 deficient mice.